Kajian Al-Qur’an dalam Perspektif Mohammed Arkoun - M. Solahudin (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2021)
The study of the Qur'an continues to develop. Nowadays, there are hermeneutics that are proposed to help Ulumul Qur'an in the process of interpreting the Qur'an. Its presence from the West often raises pros and cons. Including those who develop hermeneutics in interpreting the Qur'an is Mohammed Arkoun. He wanted to dismantle Islamic thought, including the interpretation of the Qur'an, which was actually born from the historical process. In interpreting the Qur'an, Arkoun offers synchronic exploration, diachronic exploration, anthropological perspective, and philosophical perspective and religious facts.